HGF/c-MET axis contributes to CLL cell survival by regulating multiple mechanisms making it a potential therapeutic target for CLL treatment - Liang, Shihao; Shao, Xiaoya; Meng, Xueqiong; Cui, Ying; Sun, Chuanyue; Sun, Jie; Zhang, Binghui; Shen, Guomin; Qin, Ling; Yang, Haiping; Chen, Yixiang (Frontiers in Pharmacology, 2025)
Despite significant advances in understanding the occurrence, progression and treatment of chronic lymphocytic leukemia (CLL), there remains a need to explore novel mechanisms and therapeutic strategies. In this study, we discovered that hepatocyte growth factor (HGF), a cytokine highly expressed by bone marrow mesenchymal stem cells within the microenvironment, activates the AKT, ERK and STAT3 signaling pathways, promotes the expression of anti-apoptotic proteins BCL-2, MCL-1, and BCL-xL, thereby enhancing CLL cell survival and resistance to both natural and ABT-199-induced apoptosis. Knockdown of c-MET, the unique receptor for HGF, using lentivirus-mediated shRNA, significantly attenuated the activation of these pro-survival signaling pathways and downregulated the expression of anti-apoptotic proteins in the BCL-2 family. Consequently, this inhibited CLL cell proliferation and promoted apoptosis. Similarly, pharmacological targeting of the HGF/c-MET pathway with the inhibitor capmatinib markedly suppressed the activation of pro-survival signaling pathways, reduced the expression of anti-apoptotic proteins, inhibited cell proliferation, arrested cell cycle at G0/G1 stage, induced apoptosis, and enhanced the pro-apoptotic effect of ABT-199. In summary, this study highlights the critical role of HGF/c-MET axis in CLL cell survival and demonstrates that targeting this pathway holds therapeutic potential for the treatment of CLL.